Fecal microbiota transplantation results in bacterial strain displacement in patients with inflammatory bowel diseases - Manli Zou; Zhuye Jie; Bota Cui; Honggang Wang; Qiang Feng; Yuanqiang Zou; Xiuqing Zhang; Huanming Yang; Jian Wang; Faming Zhang; Huijue Jia (FEBS Open Bio, 2020)
Fecal microbiota transplantation (FMT), which is thought to have the potential to correct dysbiosis of gut microbiota, has been used to treat inflammatory bowel disease (IBD) for almost a decade. Here, we report an interventional prospective cohort study performed to elucidate the extent of and processes underlying microbiota engraftment in IBD patients after FMT treatment. The cohort included two categories of patients: (a) patients with moderate to severe Crohn’s disease (CD) (Harvey–Bradshaw Index ≥ 7, n = 11) and (b) patients with ulcerative colitis (UC) (Montreal classification S2 and S3, n = 4). All patients were treated with a single FMT (via mid‐gut, from healthy donors), and follow‐up visits were performed at baseline, 3 days, 1 week, and 1 month after FMT (missing time points included). At each follow‐up time point, fecal samples and clinical metadata were collected. For comparative analysis, 10 fecal samples from 10 healthy donors were included to represent the diversity level of normal gut microbiota. Additionally, the metagenomic data of 25 fecal samples from five individuals with metabolic syndrome who underwent autologous FMT treatment were downloaded from a previous published paper to represent fluctuations in microbiota induced during FMT. All fecal samples underwent shotgun metagenomic sequencing. We found that 3 days after FMT, 11 out of 15 recipients were in remission (three out of four UC recipients; 8 out of 11 CD recipients). Generally, bacterial colonization was observed to be lower in CD recipients than in UC recipients at both species and strain levels. Furthermore, across species, different strains displayed disease‐specific displacement advantages under two‐disease status. Finally, most post‐FMT species (> 80%) could be properly predicted (area under the curve > 85%) using a random forest classification model, with the gut microbiota composition and clinical parameters of pre‐FMT recipients acting as factors that contribute to prediction accuracy.